Metal‐Organic Framework‐Based Materials for Aqueous Zinc‐Ion Batteries: Energy Storage Mechanism and Function. Issue 10 (30th May 2022) - Xu, Xilian; Chen, Ye; Liu, Dongshu; Zheng, Dong; Dai, Xiaojing; Shi, Wenhui; Cao, Xiehong
Abstract: Aqueous rechargeable zinc‐ion batteries (ZIBs) featuring competitive performance, low cost and high safety hold great promise for applications in grid‐scale energy storage and portable electronic devices. Metal‐organic frameworks (MOFs), relying on their large framework structure and abundant active sites, have been identified as promising materials in ZIBs. This review comprehensively presents the current development of MOF‐based materials including MOFs and their derivatives in ZIBs, which begins with Zn storage mechanism of MOFs, followed by introduction of various types of MOF‐based cathode materials (PB and PBA, Mn‐based MOF, V‐based MOF, conductive MOF and their derivatives), and the regulation approaches for Zn deposition behavior. The key factors and optimization strategies of MOF‐based materials that affect ZIBs performance are emphasized and discussed. Finally, the challenges and further research directions of MOF‐based materials for advanced zinc‐ion batteries are provided. Abstract : In this review, we outline and discuss the current development of MOF‐based materials including MOFs and their derivatives in ZIBs, especially Zn storage mechanism in MOFs, typical types as cathodes and the regulation for Zn deposition behavior. This review can give deeper insights into the relationship between the composition, structure of MOF and the performance of ZIBs and provide certain reference for the further development of MOF‐based high‐performance ZIBs.